The Types And Meaning Of Slangs Used In “Blind Side” Movie - Astuti, Ester Dwi; Mas Indrawati, Ni Luh Ketut; Parthama, I Gusti Ngurah (Humanis; Vol 17 No 3 (2016), 2017)
This paper entitled The Types and Meaning of Slangs used in The Movie Blind Side .  The aims of this paper are to identify and classify the types of slang words and describe the slang meaning of slang words. The data were collected by using the following steps, first watching Blind Side by John Lee Hancock (2009) (and based on the book The Blind Side: Evolution of a Game by Michael Lewis) repeatedly and finding the statements that reflect the slang words and phrase used in the movie. The theories applied in this study were based on the theory of slang word about Primary slang and Secondary slang stated by Chapman (1988) and seven types meaning of slang word: Conceptual or denotative meaning, Connotative, Stylistic, Affective, Reflected, Collocative and Thematic meaning stated by Leech (1973). The method used to collect data was the documentation method. And the methods of analyzing data were the descriptive and qualitative methods. The analysis showed that there were two types of slang words in Blind Side movie. They are primary slang and secondary slang. The type of slang word in Blind Side movie was mostly in the form of primary slang. From all types of meaning, Blind Side movie often used conceptual meaning or denotative meaning than other meanings were in the forms of words and phrase
Keywords: Slang, meaning, types, movie.